Rules for Electronic Meetings as Conducted via E-Mail. - Stackpole, John D. (Parliamentary Journal, 2013)
The author discusses the rules mentioned in the 11 edition of the book "Robert's Rules of Order Newly Revised" by Henry Martyn Robert regarding Electronic Meetings (e-meetings). He comments on the types of electronic media that are available for conducting electronic meetings such as Electronic-Mail (E-mail), chat rooms, and video conferencing. He also discusses the procedure of starting and ending an e-Meeting.